Inbreeding depression in crambe1 - Lara-fioreze, Ana Carolina Da Costa (2016)
ABSTRACT Inbreeding depression in plants, caused by selfing or crossing among plants with a high degree of relatedness, is a genetic phenomenon that affects quantitative traits. This study aimed at verifying the occurrence of inbreeding depression in crambe progenies originated from selfing, in comparison with open pollination progenies. A randomized blocks design, with three replications, in a 32 x 2 factorial arrangement, with 32 crambe progenies and two reproduction systems (artificial selfing and open pollination), was used. Grain yield, 1,000-grain weight, plant height and final stand were evaluated. A significant interaction was observed between progenies and reproduction systems in all traits evaluated. A reduction in grain yield, 1,000-grain weight and plant height occurred in the majority of the selfing progenies, when compared to open pollination progenies. Inbreeding depression was observed in all traits, especially for grain yield. The heritability coefficients of selfed progenies were higher than the open pollinated ones, except for 1,000-grain weight.